Mapping Inequalities in the Physical, Built and Social Environment in Population-Based Studies of Brain Health - Paus, Tomáš; Brook, Jeff; Doiron, Dany (Frontiers in Neuroimaging, 2022)
This mini-tutorial describes how combining aggregate-level data about the physical, built and social environment can facilitate our understanding of factors shaping the human brain and, in turn, brain health. It provides entry-level information about methods and approaches one can use to uncover how inequalities in in the neighborhood environment lead to health inequalities in general, and those in brain health in particular. This background knowledge should be helpful to those who are interested in using neuroimaging to investigate how environmental factors shape inter-individual variations in the human brain.